Commodity Pairs trading with dynamic cointegration - Hansen, Bård Andre (2023)
This paper investigates the efficacy of a commodity pairs trading strategy using a dynamic cointegration approach. It analyses 17 commodities futures from 2007-2022, employing a rolling cointegration method to identify mean-reverting pairs. The strategy optimizes pairs selection and utilizes cointegration as a trading signal. It demonstrates robust performance with notable risk adjusted returns, especially after selection of the top performing pairs. The study contributes to pairs trading strategies and provides insights into alternative applications of cointegration.